The Vocabulary List for ELT Textbooks in Language Acquisition and Teaching Methodology - Kim, Hyeon Okh; Lee, Hye Kyung (Korean Journal of English Language and Linguistics, 2023)
The study aims to investigate vocabulary demands in academic textbooks for ELT majors, identifying the most frequent word list for preservice teachers and variations in lexical needs across sub-areas. For the purposes, the study compiled a corpus comprising approximately 1.6 million tokens from twelve university textbooks in the integral dimensions of ELT: language acquisition and teaching methodology. By analyzing the lexical coverage of the ELT textbook corpus against the twenty-five 1,000 word-family list from the British National Corpus and Corpus of Contemporary American English (BNC/COCA), the study assessed the lexical load of ELT textbooks and developed an essential vocabulary list. Findings revealed that achieving a 95% lexical coverage in ELT textbooks necessitates mastery of the top 4,000 word families, including proper nouns, interjections, transparent compounds, abbreviations, and glossary terms. To attain 98% coverage, however, ELT students require an 11,000-word family vocabulary. Further analyses show that textbooks in language acquisition demand a higher lexical requirement compared to those in teaching methodology. By applying a set of criteria for widespread use and pedagogical relevance, the study identified 513 word families beyond the initial 2,000 levels on the BNC/COCA, constituting 9.36% of the ELT textbooks. The study suggests practical pedagogical implications.
Keywords: corpus analysis; discipline-specific word list; ELT textbooks; ELT vocabulary; ELT word list; technical vocabulary; vocabulary load